Pengaruh Literasi Keuangan terhadap Spending Behavior Mahasiswa Penerima Beasiswa Bank Indonesia - Rizki Febri Eka Pradani; Fadhillatus Sholihah; Dita Wulandari Agustin; Dia Auliatur Rohmah; Laily Fitriya; Dini Fitriani Ali (Universitas Nurul Jadid, 2025)
This study aims to analyze the effect of financial literacy on the spending behavior of Bank Indonesia Scholarship recipients at Universitas Nurul Jadid (UNUJA). The research employs a quantitative associative-causal approach with a sample of 80 scholarship recipients from 2023–2025. Data were collected through questionnaires and analyzed using simple linear regression with SPSS version 26. The results show that the financial literacy variable has a t-value of -1.344, lower than the t-table value of 2.012, with a significance level of 0.185 (> 0.05). This indicates that financial literacy has a negative but insignificant effect on students’ spending behavior. It implies that students’ financial understanding has not been fully reflected in their actual financial practices, as social factors, lifestyle, and campus environment still influence their spending patterns. This study highlights the need for more practical and value-based financial literacy programs so that scholarship recipients not only understand financial concepts but also apply them wisely and responsibly in daily life.